Synthesis of 6H-Dibenzo[b,d]pyran-6-one Derivatives via Coumarin-Fused Cyclohexa-1,3-diene Intermediates - Chen, Chao-Yue; Zhao, Yong-Sheng; Xiang, Chang-Bing; Huang, Zhi-Zhen (Synthesis, 2012)
In the presence of trifluoroacetic acid and methanesulfonic acid (MSA), a series of monohydric and polyhydric phenols readily undergo a domino Pechmann–dehydration reaction with various 4-hydroxy-6-oxocyclohexane-1,3-dicarboxylates to give 7,8-dihydro-6H-dibenzo[b,d]pyran-6-ones. Subsequent dehydrogenation of the 7,8-dihydro-6H-dibenzo[b,d]pyran-6-ones was performed expediently with DBU/BrCCl3 to give various 6H-dibenzo[b,d]pyran-6-one derivatives. This strategy has the advantages of inexpensive and easily available raw materials, metal-free procedure, mild reaction conditions, good compatibility with various functional groups, and satisfactory yields.
Keywords: 6H-dibenzo[b,d]pyran-6-one; 7,8-dihydro-6H-dibenzo[b,d]pyran-6-one; domino Pechmann–dehydration reaction; oxidative dehydrogenation; synthesis